Refining MR-guided thermal ablation for HCC within the Milan criteria: a decade of clinical outcomes and predictive modeling at a single institution - Fu-Qun Wei; Pei-Shu Huang; Bing Zhang; Rui Guo; Yan Yuan; Jin Chen; Zheng-Yu Lin (BMC Cancer)
Abstract Background The appropriateness of ablation for liver cancer patients meeting the Milan criteria remains controversial. Purpose This study aims to evaluate the long-term outcomes of MR-guided thermal ablation for HCC patients meeting the Milan criteria and develop a nomogram for predicting survival rates. Methods A retrospective analysis was conducted from January 2009 to December 2021 at a single institution. Patients underwent MR-guided thermal ablation. Factors influencing progression-free survival (PFS) and overall survival (OS) were identified using univariate and multivariate Cox regression and stepwise regression. A nomogram was developed for survival prediction, followed by risk stratification and internal validation. Adverse events (AEs) were also analyzed. Results A total of 181 patients were included, with a mean follow-up of 73.8 ± 31.7 months. The cumulative local tumor progression rates at 1, 3, and 5 years were 0.80%, 1.27%, and 1.86%, respectively. The 1-, 3-, and 5-year PFS rates were 81.8%, 57.4%, and 38.1%, and OS rates were 98.3%, 87.8%, and 62.9%. Poorer outcomes were associated with age ≤ 60 years, tumor size > 2 cm, multiple tumors, cirrhosis, proximity to major vessels, and narrow ablation margins (P < 0.05). The nomogram accurately predicted 3- and 5-year survival, and internal validation confirmed the results. AEs occurred in 33.7% of patients, with pain being the most common. Conclusion MR-guided ablation is effective for HCC patients within the Milan criteria, especially for those with smaller tumors and better liver function. The nomogram and risk stratification model are valuable tools for predicting patient outcomes and guiding treatment.